Relationship Between Mother's Knowledge And Independence Medium Mentally Retarded Child - Ima Sukmawati; Elis Noviati; Tika Tresnawati Rahayu (Yayasan Inspirasi El Burhani, 2023)
Introductions: The abilities possessed by mentally retarded children are not the same as the independent abilities possessed by normal children. Even so, it is important for mentally retarded children to carry out an activity on their own so as to reduce dependency and assistance and be able to live independently in the future. Family knowledge greatly influences efforts to increase the independence of moderately mentally retarded children. The purpose of this study was to determine the relationship between mothers' knowledge and the independence of moderately mentally retarded children at Ciamis State SLB. Aims: To determine the relationship between mothers' knowledge and the independence of moderately mentally retarded children Methods: The research design is a case-control with a retrospective approach. The population is mothers who have moderately mentally retarded children in Ciamis State SLB as many as 38 people. The sampling method uses the total population technique with regard to exclusion and inclusion criteria. The tool used is the form of a questionnaire made by the researcher himself.Results: The results show that the highest knowledge is in the excellent category, namely 24 people (63.2%), the independence of mentally retarded children, while the highest frequency is in the independent type, namely 23 people (60.5%) with a proven odds ratio (OR) value of 9,500, which means knowledge Greater mothers have children's independence in the independent category.Conclusions: there is a significant relationship between mothers' knowledge and independence of children with moderate mental retardation because the ρ value <α (0.002 <0.05). It is recommended to increase knowledge through counselling, discussion, or training about the right age to start training children with moderate mental retardation so that children are able to be independent.